Endograft Specific Haemodynamics After Endovascular Aneurysm Repair: Flow Characteristics of Four Stent Graft Systems. (October 2019) - Raptis, Anastasios; Xenos, Michalis; Spanos, Konstantinos; Kouvelos, George; Giannoukas, Athanasios; Matsagkas, Miltiadis
Abstract : Objectives: The implication of haemodynamics in the occurrence of complications after endovascular aneurysm repair (EVAR) has been raised in the literature. Different aortic stent graft configurations may lead to different haemodynamic properties. The current study deals with the post-operative haemodynamic variability between four stent graft systems with different structure, material, and type of fixation. Methods: Computed tomography data of 32 patients were used, equally distributed among the four endograft groups, namely the AFX, Endurant, Excluder, and Nellix. Velocity, wall shear stress (WSS), and helicity statistics were calculated, in regions around the flow division where disturbances are expected. The haemodynamic data were compared between and within the groups. Results: The morphology of AAAs pre-operatively did not vary significantly among the four groups. Before the flow division, lowest velocity was observed in Endurant cases and highest in Nellix cases. Endurant induced the lowest peak WSS and Nellix the highest ( p  = .03). The helicity levels were low in AFX and Nellix cases and high in Endurant and Excluder cases. After the flow division, the trend in the results was preserved. Nellix induced the highest velocity and WSS, followed closely by Excluder and AFX. There was a significant increase of helicity before and after flow division in AFX ( p <0.001, R 2 = 0.09) and Nellix ( p <0.001) cases. Conclusions: It has been shown that different types of endografts induce variable haemodynamic conditions around the flow division. The parallel limb structure, featured by Nellix, seems to induce favourable flow conditions in terms of velocity and WSS, while helical flow before the flow division is suppressed. High WSS is generally considered to be a desirable flow characteristic in endovascular devices, whereas helicity extremes (very low or high) are potentially a negative sign. Endurant, with the stiffer material and the short neck structure, was associated with the lowest blood velocity and WSS values but preserved high helicity levels. The AFX and Excluder, which include the same material, induced similar haemodynamic conditions.